PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WORDWALL PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI NEGARA KESATUAN REPUBLIK INDONESIA KELAS IV SDN KADEMANGAN 2 - Rika Wahyuni; Didit Yulian Kasdriyanto, Shofia Hattarina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low interest in learning and understanding of students caused by the minimal use of learning media. Therefore, the research attempts to create interesting learning media to improve students' understanding. This research uses the Research & Development (R&D) method with the Borg & Gall model consisting of six stages: (1) Potential and problems; (2) Planning; (3) Product Design; (4) Product validation; (5) Product revision; and (6) Product trial. The results of the study showed that the wordwall media received a score of 93% from media experts, 80% from material experts, and 92% from class teachers, all of which were in the very feasible category. The trial on students showed an increase in understanding of the material, with an average pretest score of 47.4 and a posttest of 88.4. Based on the results of this study, it can be concluded that interactive media based on wordwalls is effective in improving students' understanding and learning motivation, and is feasible to be used as an innovative learning media in Pancasila Education subjects in elementary schools. Keywords: Development; learning media; wordwall; pancasila education